Water spreading weirs altering flood, nutrient distribution and crop productivity in upstream–downstream settings in dry lowlands of Afar, Ethiopia - Getnet, M.; Amede, T.; Tilahun, G.; Legesse, G.; Gumma, Murali K.; Abebe, H.; Gashaw, T.; Ketter, C.; Akker, Elisabeth van den (Cambridge University Press, 2022)
Afar in Ethiopia is a drought prone area characterized by low rainfall, high temperature and suffering from flash flood emerging from adjacent mountains. We introduced a flood barrier, water spreading weirs (WSWs) in 2015 to convert floods to a productive use and assessed its effect in 2016 and 2017. WSWs resulted in deposition of sediments where sand deposition was higher in the upside of upstream weir whereas silt and clay deposition was prominent at the central location between the two weirs. There was a moisture gradient across farming fields with volumetric water content (VWC) at 20 cm depth varying between 10 and 22% depending on the relative position/distance of fields from the WSWs, consequently, effecting significant difference in yield between fields. There was a positive relationship between VWC made available by WSWs at planting and the yield (P < 0.001, r = 0.76) and biomass productivity (P < 0.005, r = 0.46). WSWs created differing farming zone following soil moisture regime, affecting grain and biomass yield. In good potential zones with high moisture content, the WSW-based farming enabled to produce up to 5 and 15 t ha−1 yr−1 of maize grain and biomass, respectively, while in low potential zones there was a complete crop grain failure. The system enabled pastoralists to produce huge amount of biomass and grain during Belg (short) and Meher (long) growing seasons that was stored and utilized during succeeding dry periods. Furthermore, the practice ensured a visible recovery of degraded rangelands. This was evident from the filling up of the riverbed as well as the two WSW wings with 1 m high and about 450 m length each with fertile sediment from Belg and Meher seasons of 2016 and 2017. Hence, future studies should analyze the sustainability and the potential of flood-based development at large scale.